O teste de integridade como ferramenta de combate à corrupção - Matias, Flávio Pereira da Costa (2019)
The dissertation goal is to analyse the anti-corruption tool integrity testing. In Chapter 1, we discuss the consequences of corruption, the challenges that it poses in Brazil and why should we combat corruption. Then, we study how corrupted countries had faced corruption, how the reforms have been implemented and the path to anti-corruption reforms in Brazil. In Chapter 2, we focus on the implementation of integrity testing in the private sector in Brazil, United States, and United Kingdom. In Chapter 3, we define integrity testing and analyse its types, and we do a comparative study about the integrity testing. The Chapter 4 seeks to study the integrity testing in Brazil, and its implementation possibilities. The dissertation concludes that implementation of integrity testing in Brazil is possible, despite the absence of legislation on integrity testing.